GAMBARAN TINGKAT PENGETAHUAN DAN KETERAMPILAN WANITA USIA SUBUR DALAM MELAKUKAN PEMERIKSAAN PAYUDARA SENDIRI - Martha, Maria; Pradika, Jaka; Surtikanti (Jurnal Riset Keperawatan dan Kesehatan, 2025)
Background: Breast cancer is the most common cancer in women in Indonesia. Early detection through Breast SelfExamination (SADARI) is cheap, easy, and can be done independently, but the practice in the community is still low Objective: To describe the level of knowledge and skills of women of childbearing age (WUS) in conducting SADARI in the working area of the Telaga Arum Health Center, North Kayong Regency Method: Quantitative descriptive design with a cross-sectional approach. A sample of 167 WUS was obtained by consecutive sampling (March–September 2025). Instruments: AWARE knowledge questionnaire and skills observation sheets that have been validated (r item of knowledge ≥0.610; r item of skill 0.618–0.979) and reliable (Cronbach's α knowledge 0.853; skill 0.971). Univariate analysis presents frequency and percentage distributions. Results: The majority of respondents were aged 25–34 years old (44.9%), housewives (74.9%), junior high school education (74.3%), Muslim (83.8%), Javanese (41.9%), and had no family history of cancer (100%). Knowledge level: adequate 45.51%, good 36.53%, less than 17.96%. CONSCIOUS Skills: Enough 44.91%, Less 32.93%, Good 22.16%. Conclusion: The knowledge and skills of SADARI WUS are in the sufficient category, with a good portion that is still limited. It is necessary to strengthen practice-based/demonstration-based applicative education as well as blend with community activities to convert knowledge into correct and routine skills.